Teachers’ Perspectives on Flipped Learning: A Study of Secondary School EFL Instruction in Tunisia - Amani Bouzayenne (Journal of English as A Foreign Language Teaching and Research, 2025)
This study investigates Tunisian secondary school EFL teachers’ attitudes toward flipped learning. It explores their perceptions of its effectiveness in promoting learner engagement, language skill development, and autonomy, as well as their views on challenges related to classroom adequacy, workload, and confidence in implementation. A quantitative descriptive design was employed with data collected through a structured questionnaire completed by 33 teachers. Descriptive statistics were presented using pie charts, box plots, and bar charts. Findings reveal that most teachers were familiar with flipped learning and expressed highly positive perceptions of its potential benefits for engagement, skill enhancement, and learner autonomy. However, many regarded it as unsuitable for the secondary school level. Teachers also reported low confidence in applying the method and expressed mixed opinions on its impact on workload. The study concludes that a gap persists between theoretical support for flipped learning and its practical adoption, largely due to contextual and infrastructural constraints. To address this, it recommends targeted professional training, greater access to technological resources, and the implementation of pilot programs to promote sustainable integration.